Pelatihan Pengelolaan Event Hybrid dan Online bagi Karyawan Event Organizer - Nurhadi Surojudin; Sufajar Butsianto; Dwi Indra Prasetya; Fibi Eko Putra; Rizal Ainun Yaqin (VINICHO MEDIA PUBLISINDO, 2026)
The rapid advancement of digital technology has transformed the event organizer industry from conventional face-to-face events into hybrid and online event models. This transformation requires improved human resource competencies, particularly in digital technology, event management, and digital service marketing. This community service program aims to enhance the competencies of employees at PT. Seirah Wisata Ali Takrim in managing hybrid and online events through structured training and mentoring activities. The implementation method consists of socialization, hands-on training, technology implementation through event simulations, mentoring, evaluation, and sustainability planning. The training materials cover digital event production, operational event management, the development of Standard Operating Procedures (SOPs), and digital marketing strategies. The expected outcomes include improved technical competencies of participants, the availability of SOPs for hybrid and online event management, the development of competitive digital service packages and event portfolios, as well as enhanced service quality and organizational competitiveness in the digital event industry. This program is expected to support the company's digital transformation while strengthening collaboration between higher education institutions and industry partners.